Sowing properties of sunflower seeds of Talento hybrid under the influence of a modified plant growth regulator - Pokoptseva Liubov; Onyshchenko Olha; Gamayunova Valentyna; Gerasko Тetiana; Zoria Mykhailo; Покопцева, Любов Анатоліївна; Онищенко, Ольга Вячеславівна; Гамаюнова, Валентина Василівна; Герасько, Тетяна Володимирівна; Зоря, Михайло Віталійович (Житомир : Поліський національний університет, 2024)
EN: The improvement of agricultural crop cultivation technologies enables the production of high sunflower yields with high-quality indicators. One such element is pre-sowing seed treatment. This study aimed to investigate the effect of a plant growth regulator supplemented with calcium on the sowing properties of sunflower seeds. The experiment was conducted under laboratory conditions. For pre-sowing seed treatment, a semi-synthetic film-forming agent with an anti-stress effect was used, which was modified with Ca2+ ions in the form of calcium chloride. It was established that the encrustation of sunflower seed with a growth regulator stimulates germination processes and activates the initial stages of sunflower organogenesis. This increases the indicators of germinative vigour and germination capacity. Adding calcium to the plant growth regulator contributes to a further increase in the indicators of germinative vigour and seed germination capacity of sunflowers by 5.4% and 7.7%, respectively, compared to the control. At the same time, the hypocotyl length increased by 1.51 times compared to the control, while the root length increased by 1.37 times. The accumulation of organic substances in sunflower seedlings is characterised by an increase in dry matter. When calcium was added to the plant growth regulator, a more intensive accumulation of dry matter in the hypocotyl and root was observed compared to the control and the variant using only the growth regulator. The establishment of a ranking range indicated that, based on the parameters studied, the optimal treatment option for the pre-sowing treatment of sunflower seeds is the application of a plant growth regulator containing calcium ions at a concentration of 1.0 g/L. The use of this preparation is relevant and promising for studying the formation of sunflower plant productivity with increased quality indicators under field conditions. UA: Удосконалення технологій вирощування сільськогосподарських культур дає змогу отримувати високі врожаї соняшнику з високими показниками якості. Одним з таких елементів є передпосівна обробка насіння. Метою досліджень було вивчення впливу регулятора росту рослин з додаванням кальцію на посівні властивості насіння соняшнику. Дослід проведений у лабораторних умовах. Для передпосівної обробки насіння використовували напівсинтетичний плівкоутворюючий препарат антистресової дії, який модифікували іонами Са2+ у вигляді хлориду кальцію. Було встановлено, що інкрустація насіння соняшнику регулятором росту стимулює процеси проростання і активізує початкові етапи органогенезу соняшнику. При цьому збільшуються показники енергії проростання і схожості насіння, спостерігається збільшення довжини гіпокотилю і довжини кореня. Додавання кальцію до регулятору росту рослин сприяє додатковому збільшенню показників енергії проростання і схожості насіння соняшнику на 5,4 % і 7,7 %, порівняно з контролем. При цьому довжина гіпокотилю збільшується відносно контролю у 1,51 рази, а довжина коренів у 1,37 рази. Накопичення пластичних речовин у проростках соняшнику характеризує приріст сухої речовини. При додаванні кальцію до регулятора росту рослин спостерігається більш інтенсивне накопичення сухої речовини гіпокотилю і сухої речовини кореня, порівняно з контролем і варіантом досліду з використанням тільки регулятору росту. При побудуванні ранжируваного ряду встановлено, що за досліджуваними показниками для передпосівної обробки насіння соняшнику оптимальним варіантом досліду є варіант обробки регулятором росту рослин з вмістом іонів кальцію 1,0 г/л. Використання даного препарату є актуальним і перспективним для вивчення формування продуктивності рослин соняшнику з підвищеними показниками якості у польових умовах.
Посівні властивості насіння соняшнику гібриду Talento за дії модифікованого регулятору росту рослин
Keywords: germinative vigour; germination capacity; calcium; seedling length; dry matter; ranking range; енергія проростання; схожість; кальцій; довжина проростків; суха речовина; ранжируваний ряд